Effect of Storage Conditions on the Chemical Composition of Vietnamese Clove (Syzygium aromaticum) Essential Oil - Mai Huynh Cang (Journal of Global Pharma Technology, 2016)
In this study, changes in the composition of the oil from clove buds (Syzygium aromaticum) and their blends were investigated by mass gas chromatographic analysis during different storage under light and temperature conditions for a period of four months. Samples that were taken periodically were used to assess the chemical composition. Under these conditions, clove essential oil retains its main ingredients, including Eugenol, β-Caryophyllene and Acetyleugenol for four months. However, the oxidation rate of the essential oil under direct light and 45 ° C is rapid, contrasted by that essential oils stored in the dark and 4 ° C. The total Eugenol content in essential oils increased further at the end of the storage period under storage conditions. Changes in these compounds during storage can serve as an indicator of quality for clove essential oil.Keywords: Syzygium aromaticum, Essential oïl, Storage, Temperature, Light, Oxidation.